Pengaruh Pemberian PGPR Dari Beberapa Jenis Akar Bambu Untuk Menekan Penyakit Layu Bakteri Pada Cabai Besar - Emilya, Riska; Marsuni, Yusriadi; Fitriyanti, Dewi (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
This research aims to identify the source of PGPR from four types of bamboo roots that are effective in suppressing the incidence of R. solanacearum bacterial wilt disease in large red chili plants. The method used in this research was a Completely Randomized Design (CRD) involving 4 treatments and 1 control. The treatments are P0 = Control (Without PGPR application); P1 = PGPR from Banar/Rabungan Bamboo Roots; P2 = PGPR from Tali Bamboo Roots; P3 = PGPR from Tamiang Bamboo Roots; and P4 = PGPR from Haur Bamboo Roots. Each treatment was repeated 4 times, 20 experimental units. Each experimental unit consisted of 10 plants, so the total plants used were 200 and all of them were used as samples. To measure the effect of administering PGPR from various types of bamboo roots on the variables Disease Incidence, Number of Fruit, and Fruit Weight, disease incidence was observed every 7 days after the initial symptoms appeared, and observations of the number and weight of fruit were carried out 7 harvests at intervals of 5 days. Observation results showed that treatment with Tamiang Bamboo Root (Schizoseyum blumei) (P3) was superior to other treatments.